Success Factors for Reducing Maternal and Child Mortality - Kuruvilla, Shyama (World Health Organization, 2015)
Reducing maternal and child mortality is a priority in the Millennium Development Goals (MDGs), and will likely remain so after 2015. Evidence exists on the investments, interventions and enabling policies required. Less is understood about why some countries achieve faster progress than other comparable countries. The Success Factors for Women’s and Children’s Health studies sought to address this knowledge gap using statistical and econometric analyses of data from 144 low- and middle-income countries (LMICs) over 20 years; Boolean, qualitative comparative analysis; a literature review; and country-specific reviews in 10 fast-track countries for MDGs 4 and 5a. There is no standard formula – fast-track countries deploy tailored strategies and adapt quickly to change. However, fast-track countries share some effective approaches in addressing three main areas to reduce maternal and child mortality. First, these countries engage multiple sectors to address crucial health determinants. Around half the reduction in child mortality in LMICs since 1990 is the result of health sector investments, the other half is attributed to investments made in sectors outside health. Second, these countries use strategies to mobilize partners across society, using timely, robust evidence for decision-making and accountability and a triple planning approach to consider immediate needs, long-term vision and adaptation to change. Third, the countries establish guiding principles that orient progress, align stakeholder action and achieve results over time. This evidence synthesis contributes to global learning on accelerating improvements in women’s and children’s health towards 2015 and beyond.